2019
DOI: 10.1186/s13063-018-3057-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a hydrogel dressing as an analgesic adjunct to first aid for the treatment of acute paediatric thermal burn injuries: study protocol for a randomised controlled trial

Abstract: BackgroundBurns are a painful and traumatic experience, particularly in children. Reduced pain and anxiety positively influences re-epithelialisation rates in paediatric burn patients, however current literature fails to fully explain the effects of pain and anxiety and their links with wound healing. This study will determine if Burnaid® hydrogel dressing is an effective treatment for reducing pain in the acute period of a burn injury. It is hypothesised that a reduction in pain will then improve re-epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 62 publications
0
8
0
3
Order By: Relevance
“…9 The literature indicates that cooled hydrogel dressings reduce pain when applied on wounds. 10 During PRP therapy, we performed approximately 30 to 50 small injections lacerating a large surface of the facial skin. This led to needle prick-induced pain despite previous application of numbing cream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 The literature indicates that cooled hydrogel dressings reduce pain when applied on wounds. 10 During PRP therapy, we performed approximately 30 to 50 small injections lacerating a large surface of the facial skin. This led to needle prick-induced pain despite previous application of numbing cream.…”
Section: Discussionmentioning
confidence: 99%
“…Several forms, including solid sheets or semi‐liquid gels are available 9 . The literature indicates that cooled hydrogel dressings reduce pain when applied on wounds 10 . During PRP therapy, we performed approximately 30 to 50 small injections lacerating a large surface of the facial skin.…”
Section: Discussionmentioning
confidence: 99%
“…Study methodology was documented in a published protocol 18 and registered with the Australian New Zealand Clinical Trials Registry (ID number: ACTRN12617001274369) on the 5 September 2017 prior to recruitment. This trial was completed as per the published protocol, 18 which contains a more in-depth description of the trial’s design and methods.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that a treatment delay greater than five days for cartilage infections can lead to severe outcomes, such as impaired hearing, ear deformation, and amputation of the auricle [ 10 ]. There has been much effort to prevent infection resulting from wounds by administering a wide range of active agents to the wound locally: these agents include anti-infective [ 12 , 13 , 14 ], anti-inflammatory [ 15 , 16 , 17 ], and analgesic [ 18 , 19 , 20 ] compounds. The common aftercare practice for preventing ear piercing infection is the regular application of antiseptics or antibiotics [ 18 , 21 , 22 , 23 , 24 ] for a few weeks, which is not thoroughly effective as nearly 20% of all piercings lead to local infection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%